Hamlin Garland : a life - Newlin, Keith (University of Nebraska Press, 2008)
The first and only other biography of Hamlin Garland was published more than forty years ago; since then, letters, manuscripts, and family memoirs have surfaced to provide, along with changing literary scholarship, a more evaluative and critical interpretation of Garland?s life and times. Hamlin Garland: A Life is an exploration of Garland?s contributions to American literary culture and places his work within the artistic context of its time.